Koefisien Perpindahan Panas Permukaan Bola dengan Aliran Udara Paksa dalam Pipa - B. Rahardjo; B. Suratmo; Sukarjo Sukarjo (agriTECH, 1998)
Handling and processing of agricultural products mostly consist of heat transfer. Commonly the heat process of agricultural products is conducted in closed systems with air forced circulation. The process of heat transfer is significantly controlled by the values of the coefficient of surface heat transfer. Therefore the objectives of the research were to determine the pertinent parameters affecting the coefficient of heat transfer of sphere in forced air circulation and then to develop the mathematical relationship of those parameters. The mathematical relationship was determined using dimensional analysis composing dimensionless numbers such as Nusselt, Reynolds and size ratio. The coefficient of surface heat transfer were determined by heat capacitance method and analytical approaches using samples of spheres made from copper and wood respectively. The results indicate that the relation of the dimensionless groups were significant. The coefficient of surface heat transfer appropriately can be expressed using the pertinent parameters.